Kemampuan Bahasa Asing Pengelola Pariwisata dan Pengaruhnya Terhadap Ketahanan Ekonomi di Pangkalpinang, Bangka Belitung - Saputra, Putra Pratama; Fatah, Abdul; Pratama, Sandy (Jurnal Ketahanan Nasional, 2025)
ABSTRACT Pangkalpinang is ‘the main gate’ into Bangka Belitung province for the tourists from various destinations, both domestic and foreign. Physical infrastructure and human resources become one of the important prerequisites to make Bangka Belitung ready become a ‘global tourism destination’. This study aims to map and track the foreign language capacity of tourism actors in Pangkalpinang and try to find out the interesting things related to the condition of foreign language literacy. Through an analytical qualitative approach with a descriptive approach reinforced by mini surveys, FGDs, and in-depth field interviews, the study ultimately found that foreign language capacity, especially English, has been found to be approximately 30 tour guides who can speak English, even though their ability is still very limited. There are four Mandarin speakers, and one German speaker. Meanwhile, tour operators in hotels, museums, and disbudpar are generally able to speak English. However, the condition is still very minimal. It is due to their basic ability to communicate during short meetings only, and on average it is still with a memorization system. This condition is very influential on the development of regional tourism which automatically affects the economic resilience in Pangkalpinang